Penerapan Metode Speed Reading dalam Pembelajaran Membaca untuk Menigkatkan Hasil Belajar Siswa di SMKN 3 Takalar - Rahmat Hasan (ESTETIK : Jurnal Bahasa Indonesia, 2024)
The purpose of implementing the speed-reading method in the learning process of reading at SMKN 3 Takalar Class X TKJ 3 is to enhance students’ speed-reading skills and learning outcomes. Classroom action research is the type of research employed in this study. The data analysis techniques used are both qualitative and quantitative descriptive analyses. According to the research findings, the process of learning to read using the speed-reading method improved the learning results of the students in which in cycle 1 meeting 1 the results obtained an active percentage of 64% and this increased in the second meeting to 72%. In cycle II, the student activeness at meeting 1 achieved 80% and increased at the second meeting to 83%. Meanwhile, the results of students' reading ability in cycle 1 obtained an average score of 72 with a completion percentage only 10 or 50% of students in the complete category, and as many as 10 or 50% of students in the incomplete category. Besides, in cycle 2 students obtained an average score of 81 with a completion percentage of 20 or 100% of students obtained a complete score. To conclude, implementing the speed-reading method can improve the learning outcomes of students at class X TKJ 3 SMKN 3 Takalar.